Cultural transmission of work-welfare attitudes and the intergenerational correlation in welfare receipt - Juan D. Barón; Deborah A. Cobb-Clark; Nisvan Erkal (Institute for the Study of Labor (IZA), 2008)
This paper considers the potential for the cultural transmission of attitudes toward work, welfare, and individual responsibility to explain the intergenerational correlation in welfare receipt. Specifically, we investigate whether 18-year olds' views about social benefits and the drivers of social inequality depend on their families' welfare histories. We begin by incorporating welfare receipt into a theoretical model of the cultural transmission of work-welfare attitudes across generations. Consistent with the predictions of our model, we find that young people's attitudes towards work and welfare are shaped by socialization within their families. Young people are more likely to oppose generous social benefits and adopt an internal view of social inequality if their mothers support these views, if their mothers were employed while they were growing up, and if their families never received welfare. These results are consistent with - though do not definitively establish - the existence of an intergenerational welfare culture.
urn:nbn:de:101:1-2009011936
Keywords: I38; H31; Z1; 330; Cultural transmission; attitudes; intergenerational welfare receipt; Arbeitsethik; Sozialethik; Meinung; Generationenbeziehungen; Sozialhilfeempfänger; Sozialisation; Australien